2016
DOI: 10.1002/art.39624
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Exercise Improves Molecular Pathways of Aerobic Metabolism in Patients With Myositis

Abstract: Objective Endurance exercise demonstrates beneficial effects in polymyositis/dermatomyositis (PM/DM); however, the molecular effects of exercise on skeletal muscle are incompletely understood. We undertook this controlled pilot study to investigate the effects of a 12‐week endurance exercise training program on the molecular profile of skeletal muscle in patients with established PM/DM compared to a nonexercised control group of patients with established PM/DM. Methods Fifteen patients (7 in the exercise group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 48 publications
3
65
0
3
Order By: Relevance
“…Previous studies have shown that endurance exercise improves mitochondrial function by increasing expression of components required for oxidative phosphorylation . This was seen at the functional level in myositis patients with exercise resulting in increased aerobic capacity after 12 week .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies have shown that endurance exercise improves mitochondrial function by increasing expression of components required for oxidative phosphorylation . This was seen at the functional level in myositis patients with exercise resulting in increased aerobic capacity after 12 week .…”
Section: Resultsmentioning
confidence: 87%
“…Deidentified PM and DM biopsies ( n = 8) and healthy muscle biopsies ( n = 4) were obtained from Dr Ingrid Lundberg, Karolinska Institutet for exercise studies as described previously . In brief, muscle biopsies were frozen in liquid nitrogen‐cooled isopentane, and stored at −80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not discussed in detail, small noncoding RNA molecules such as microRNA are also important contributors to exercise-regulated posttranscriptional modulation and represent an exciting area for future investigation in epigenetic control of the exercise response (as systematically reviewed in Flowers et al 2015). (Schild et al 2015), myositis (Munters et al 2016), and type 2 diabetes (T2D) (Hussey et al 2013) relevant to muscle metabolic health has been uncovered using proteomics. Bioinformatics analysis of network adaptations has revealed important exercise variables underlying skeletal muscle (Padrao et al 2016) and heart (Ferreira et al 2015) plasticity.…”
Section: Omics and Exercise Research Tracksmentioning
confidence: 99%
“…For patients with a coexistent interstitial lung disease cyclophosphamide or tacrolimus are recommended [282,283]. Structured exercise programs have shown positive short term effects on muscle strength, and also to have favorable effects on gene expression and capillary density in muscles, of IIM patients [284,285].…”
Section: Therapymentioning
confidence: 99%